(untitled) - Togo (Tokyo, 1977)
Vinegar is not only used as seasoning but has wide use as a foodstuff. It is also made into good usr for the people's daily health.
Keywords: Rice vinegar,Y học cổ truyền,Giấm gạo,Traditional medicine